Hippobroma longiflora L Leaves as a Natural Inhibitor of Cataract Progression: A Comprehensive Study Integrating Ethanol Extract, HPLC, and Molecular Docking Approaches - Eva Imelda; Ulfa Fitria; Ulmiza Putri Mutia; Syahrul Syahrul; Masitha Dewi Sari; Sarra Mutiara Adev; Alya Mutiara Adev; Zakiaturrahmi Zakiaturrahmi; Navneet Shamsundar Toshniwal (Graha Primera Saintifika, 2023)
Cataract remains the highest preventable cause of blindness in the world. The H. longiflora plant (Hippobroma longiflora L) is a plant that has empirically been widely used to treat a variety of eye diseases including cataract. This plant has high antioxidant activity due to its high phenolic and flavonoid content. The H. longiflora plant was extracted using an ethanol solvent and its compound content was analyzed using GCMS and phytochemistry analysis. The extracts obtained were tested with TPC, TFC, antioxidants and quercetine compound with HPLC. From phytochemical and GCMS analysis, it was found that triterpenoid compounds were not found in the sample, and the compound 1-Isobutyl-2,5-dimethyl-4-phenyl-piperidin-4-ol was the most abundant (37.77%), as well as 4-Penten-1-ol, 5-phenyl-3-pperidino (1,30%) were the least abundant in the ethanol extract of the H. longiflora leaves extract. The total phenolic, flavonoid and HPLC results of quercetin were 139.21 mg GAE/g; 11.48 mg QE/G and 0.009 mg/G. Meanwhile, in an antioxidant activity test, it was found that the ethanol extract of the H. longiflora leaves has very strong antioxidants. This finding revealed the potential of ethanol extracts of H. longiflora leaves as a cataract inhibitor through its process as an antioxidant.